A review of literature on the eastern Fulani: Niger, Nigeria, Cameroon, Chad - Philippson, G. (International Livestock Centre for Africa, 1978)
Summarizes the available information on territoriality, mobility patterns & economy of the eastern groups of Fulfulde speakers with particular reference to the composition of social units, patterns of transhumance, social composition of the domestic group and size & structure of their herds.